Mapping potential connections between Southern Africa’s elephant populations - Huang, Ryan M.; van Aarde, Rudi J.; Pimm, Stuart L.; Chase, Michael J.; Leggett, Keith (PLOS ONE, 2022)
Southern Africa spans nearly 7 million km2 and contains approximately 80% of the world’s savannah elephants (Loxodonta africana) mostly living in isolated protected areas. Here we ask what are the prospects for improving the connections between these populations? We combine 1.2 million telemetry observations from 254 elephants with spatial data on environmental factors and human land use across eight southern African countries. Telemetry data show what natural features limit elephant movement and what human factors, including fencing, further prevent or restrict dispersal. The resulting intersection of geospatial data and elephant presences provides a map of suitable landscapes that are environmentally appropriate for elephants and where humans allow elephants to occupy. We explore the environmental and anthropogenic constraints in detail using five case studies. Lastly, we review all the major potential connections that may remain to connect a fragmented elephant metapopulation and document connections that are no longer feasible.